2014
DOI: 10.1111/j.1532-950x.2014.12144.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Phosphorylated Neurofilament Subunit NF‐H as a Prognostic Biomarker in Dogs With Thoracolumbar Intervertebral Disc Herniation

Abstract: Serum pNF-H levels might be a biomarker for predicting prognosis of canine SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…Nishida et al (2012) demonstrated that in dogs with degenerative disc 298 disease (DDD; n=60), pNF-H levels rose incrementally with the grade of injury severity observed 299 (62). This study also demonstrated that those animals with the highest serum pNF-H levels at veterinary presentation post-SCI were not able to regain the ability to walk following surgery (62). …”
supporting
confidence: 56%
See 1 more Smart Citation
“…Nishida et al (2012) demonstrated that in dogs with degenerative disc 298 disease (DDD; n=60), pNF-H levels rose incrementally with the grade of injury severity observed 299 (62). This study also demonstrated that those animals with the highest serum pNF-H levels at veterinary presentation post-SCI were not able to regain the ability to walk following surgery (62). …”
supporting
confidence: 56%
“…SCI has been shown to result in increased levels of pNF-H in the CSF and blood of humans, rats and 289 canines (9,34,61,62), as assessed using ELISA. In rat serum for example, no pNF-H can be detected, 290 using ELISA, in uninjured and sham injured animals, however, severe experimental SCI results in 291 high levels of measurable pNF-H (34).…”
mentioning
confidence: 99%
“…[20][21][22] However, neither of those methods alone provides prognostic accuracy superior to that of testing for deep pain perception. Measurement of various biomarker concentrations in serum or CSF [23][24][25][26] holds considerable promise for future prognostication but is insufficiently sensitive and specific at present.…”
Section: Confidence Interval Ivdhmentioning
confidence: 99%
“…In SCI dogs, blood levels of phosphoNFs were positively correlated with the severity of the injury. As an example, animals with higher levels of phosphoNFs in the serum did not regain walking ability even after corrective surgery [37]. In humans, phosphoNFs were detected in the CSF of SCI patients, higher levels being associated with more severe injuries and poorer outcomes [38,39].…”
Section: Structural Biomarkersmentioning
confidence: 99%